1990
DOI: 10.1002/1097-0142(19900515)65:10<2307::aid-cncr2820651024>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Salivary duct carcinoma (cribriform salivary carcinoma of excretory ducts) a clinicopathologic and immunohistochemical study of 12 cases

Abstract: Salivary duct carcinoma (cribriform salivary carcinoma of the excretory ducts [CSCED]) is an uncommon malignant tumor which occurs predominantly in men (83% in this series; mean age, 61 years) and most often in the parotid gland (92% in this series). The outcome is unfavorable for most patients; of 11 of 12 patients with follow-up, 45% had local recurrence, 54% had distant metastasis, and 45% were dead of disease within 10 years of diagnosis (mean, 3 years). Metastases to lymph nodes were common (72%). Immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
4
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(97 citation statements)
references
References 15 publications
6
85
4
2
Order By: Relevance
“…LG-SDC and conventional SDC are composed of neoplastic cells with ductal phenotype and varying degree of apocrine differentiation and AR expression [1,6,14,31,41] but exhibit significant clinicopathologic differences including the expression of S100 protein, with 84 % of LG-SDCs positive for S100 protein. In contrast, the data regarding S100 protein expression in conventional SDC is more controversial with Lewis et al [30] reporting expression in only 4 % while Brandwein et al [42] reported reaction in 100 % of cases. The presence of at least focal LG-SDC has not been described in any study of conventional SDC.…”
Section: Discussionmentioning
confidence: 97%
“…LG-SDC and conventional SDC are composed of neoplastic cells with ductal phenotype and varying degree of apocrine differentiation and AR expression [1,6,14,31,41] but exhibit significant clinicopathologic differences including the expression of S100 protein, with 84 % of LG-SDCs positive for S100 protein. In contrast, the data regarding S100 protein expression in conventional SDC is more controversial with Lewis et al [30] reporting expression in only 4 % while Brandwein et al [42] reported reaction in 100 % of cases. The presence of at least focal LG-SDC has not been described in any study of conventional SDC.…”
Section: Discussionmentioning
confidence: 97%
“…This may represent precursor ductal carcinoma in situ or cancerization of native preexisting excretory ducts. Prognostically favorable pathologic observations include an intraductal component comprising greater than 90% of the tumor and smaller tumor size of less than 2-3 centimeters (95,96). Discrimination from the rarely reported purely intraductal high grade carcinoma may require immunohistochemistry to clarify (78,79).…”
Section: Salivary Duct Carcinomamentioning
confidence: 99%
“…Brandwein and colleagues' review of 58 cases demonstrated 55% of patients dead of disease within a mean of 29 months (96). Therefore, these cancers are treated aggressively with complete excision, radical neck dissection and postoperative radiation therapy.…”
Section: Salivary Duct Carcinomamentioning
confidence: 99%
“…1985) and Wharton's duct (Dardick 1996b), but are more often a component of salivary duct carcinoma (Brandwein et al, 1990;Garland et al, 1984;Hui et al, 1986). In situ carcinoma is also part of the cytologic and histologic spectrum of carcinoma ex pleomorphic adenoma (Brandwein et al, 1996;LiVolsi and Perzin, 1977;Yamamoto et al, 1996Yamamoto et al, , 1998.…”
Section: Dardick Et Almentioning
confidence: 99%